Social work in the face of new challenges: blended families. Athenea Digital - Domínguez-de-la-Rosa, Laura; Millán-Franco, Mario (Universitat Autònoma de Barcelona, 2023)
In this study, we focused on blended families, which are a family type that is becoming increasingly widespread. The scarcity of current information on this type of family justifies scientific interest, but also means that there is a lack of appropriate social policies that address this phenomenon. Thematic analysis was used as the research tool. A total of 12 semi-structured interviews were conducted with members of blended families. Based on these interviews, three themes were developed: “What influences the decision to start a new family?”, “Challenges to the family configuration: normalisation strategies” and “New ways of understanding family ties”. The results suggest that these families are still built around the basic pillar of heteronormativity. Thus, further research is needed on this new family model, while pressing for more legal norms that are aligned with the new family realities. Social workers should promote the acceptance of blended families through community education.
El trabajo social ante los nuevos desafíos: las familias reconstituidas
Keywords: Familia; Family; Social Work; Thematic analysis; Applied research; Familias reconstituidas